2021
DOI: 10.1093/aob/mcab014
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate storage in herbs: the forgotten functional dimension of the plant economic spectrum

Abstract: Background and Aims Although the plant economic spectrum seeks to explain resource allocation strategies, carbohydrate storage is often omitted. Belowground storage organs are the centre of herb perennation, yet little is known about the role of their turnover, anatomy, and carbohydrate storage in relation to the aboveground economic spectrum. Methods We collected aboveground traits associated with the economic spectrum, stor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 71 publications
0
16
1
Order By: Relevance
“…This woodiness connected with structural strength and production of new covering tissue (bark) seems to convey some benefit in frost resistance (Lubbe & Henry, 2020). Woody structures can vary in their amount of both structural lignified tissue and softer storage tissue (parenchyma); parenchyma can provide greater storage carbohydrate concentration (Lubbe et al., 2021), but this storage can also occur in highly lignified tissue. The arrangement of storage tissue within woody structures can also facilitate greater mobility of water‐soluble carbohydrates and the rescue from vascular embolism caused by both frost and drought (Morris et al., 2016; Plavcová et al., 2016; Trifilò et al., 2019).…”
Section: The Perennating Organs Of Herbs In An Ecological Contextmentioning
confidence: 99%
“…This woodiness connected with structural strength and production of new covering tissue (bark) seems to convey some benefit in frost resistance (Lubbe & Henry, 2020). Woody structures can vary in their amount of both structural lignified tissue and softer storage tissue (parenchyma); parenchyma can provide greater storage carbohydrate concentration (Lubbe et al., 2021), but this storage can also occur in highly lignified tissue. The arrangement of storage tissue within woody structures can also facilitate greater mobility of water‐soluble carbohydrates and the rescue from vascular embolism caused by both frost and drought (Morris et al., 2016; Plavcová et al., 2016; Trifilò et al., 2019).…”
Section: The Perennating Organs Of Herbs In An Ecological Contextmentioning
confidence: 99%
“…3). Lubbe et al (2021) also found a significant positive correlation between below-ground stored carbohydrate concentration and leaf economic traits, particularly plant height, of 78 temperate herbs. These results on the positive influence of USO size on growth accord with widespread knowledge in the horticultural industry that plants with large bulbs or tubers produce are the most vigorous, producing the highest number of leaves, flowers, and clonal offspring (e.g.…”
Section: Discussionmentioning
confidence: 74%
“…The diverse suite of forbs co-occurring with grasses in South African mesic grassland has coevolved with recurrent dry season (winter to early spring) fires fuelled by senescent grass phytomass accumulated in the growing season (Everson et al, 1988;Bond et al, 2003). Forbs resprout rapidly after a burn from buds on underground storage organs (USOs), such as woody rootstocks, bulbs, or corms (Uys, 2006;Zaloumis and Bond, 2016;Klimešová et al, 2019), that protect growing perennating buds from fire and frost while providing a store for energy for rapid regrowth of leaves and inflorescences in spring (Dafni et al, 1981;Clarke et al, 2013;Pausas et al, 2018;Lubbe et al, 2021). Consequently, mesic grassland forbs can consequently withstand frequent topkill by frost, fire, or mowing (Fynn et al, 2004;Morris et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…It is not yet clear what caused those differences but storage organ anatomical structure might give greater insight to storage strategy (Lubbe, Klimeš, et al, 2021). For example, in trees, carbohydrate concentration correlated with the percentage of parenchyma in xylem rays (Plavcová et al, 2016) but the same relationship was not confirmed in herbs (Lubbe, Klimeš, et al, 2021).…”
Section: Storage Organs and Carbohydrate Contentmentioning
confidence: 97%
“…According to some researchers, storage is a vital part of plant strategy (Gomes de Moraes et al, 2016;Howard & Cellinese, 2020;Pausas et al, 2018), to others it is merely the deposition of surplus carbon because of restricted growth in nutrient poor, cold or otherwise stressful environments (Prescott et al, 2020). This lack of consensus on the role of storage is surprising because carbon storage is part of plant economy (Lubbe, Klimeš, et al, 2021)-the cornerstone of plant lifehistory strategies (Salguero-Gómez et al, 2016;Wright et al, 2004).…”
Section: Introductionmentioning
confidence: 99%